Online education: new ideas - Voevodin, V.V.; Voevodin, Vl.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2003)
Experience on creation of educational software is discussed for the two branches of mathematics: linear algebra and parallel computing. The necessity of producing hierarchical sets of educational materials and the provision of interchangeability for their print and online versions are emphasized. For online educational software, we propose new ideas for their construction; these ideas are based on a deep structurization of material and on the introduction of cause-and-effect relations.